Merchant of venice - King, Charles Percy (My University, 1898)
Introduction: The Merchant of Venice opens with a street scene and the presentation of Antonio. He is a rich merchant, a man of peculiar characteristics. He is engaged in a vast commerce, which is constantly adding to his wealth. He is a warm hearted, easy going man, easily imposed upon, and willing to do anything for a friend. When Bassanio comes to him to loan money, he loans it to him without a murmur. Bassanio is a young spendthrift, noble, who, to preserve appearances, has lived far beyond his means. He is not vicious nor depraved but simply unpractical. He has borrowed often from Antonia, and feels somewhat delicate in asking for more money; but being in need of money, and knowing no other source; he goes to Antonia once more, telling him of his plans. He speaks of a lady of Belmont who is fair, has many virtues, and is vastly rich, saying that he aspires for her hand and telling Antonia “There are many who know her worth, and had I means to hold a rivals place.”
Citation: King, Charles Percy. Merchant of venice. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Merchant; Venice; Commerce; Wealth; Theses; Manuscripts (documents)